Development of unmanned remote smart rescue platform applying Internet of Things technology - Jung Woo Kim; Sang Hun Sul; Jae Boong Choi (International Journal of Distributed Sensor Networks)
A new form of network has been created with the communication between objects in the Internet of Things environment. Users began to take interests in outdoor activities such as sports and leisure activities while sharing photographs and videos each other. In order to minimize the damage caused by unexpected accidents in response to outdoor climate change, Internet of Things technology is applied to emergency rescue system for quick and efficient rescue. In this article, the unmanned remote smart rescue platform applying Internet of Things technology quickly responds by real-time monitoring of the occurrence of a distress call. The system was developed so that the emergency situation is transferred to the management center and rescue victims within 4 min. The real-time monitoring system of unmanned remote smart rescue box is developed in such a manner that the equipment can be checked for theft and damage from external sources. Sensor multifunction printed circuit board module is developed under Internet of Things environment to be interconnected to single-board computers and various sensors. Thus, the installation of unmanned remote smart rescue box at the actual site delivers accurate positions of rescuees to promptly dispatch personnel to carry out efficient rescue operations.